Influence of Light Intensity on Methanotrophic Bacterial Activity in Petit Saut Reservoir, French Guiana - Dumestre, J. F. (American Society for Microbiology, 1999)
One year after impoundment in January 1994, methanotrophic bacteria in Petit Saut Reservoir (French Guiana) were active at the oxic-anoxic interface. This activity was revealed by the sudden extinction of diffusive methane emission (600 metric tons of CH(4) · day(−1) for the whole lake surface area, i.e., 360 km(2)). Lifting of inhibition was suspected. After reviewing the potential inhibitors of this physiological guild (O(2), NH(4)(+), sulfides) and considering the similarities with nitrifiers, we suggest that sunlight influenced the methanotrophic bacteria. On the basis of phospholipid analysis, only a type II methanotrophic community was identified in the lake. Both growth and methanotrophic activity of an enriched culture, obtained in the laboratory, were largely inhibited by illumination over 150 microeinsteins · m(−2) · s(−1). These results were confirmed on a pure culture of Methylosinus trichosporium OB3B. In situ conditions showed that water transparency was quite stable in 1994 and 1995 and that the oxycline moved steadily deeper until January 1995. Considering the mean illumination profile during this period, we showed that removal of methanotrophic growth inhibition could only occur below a 2-m depth. The oxycline reached this level in October 1994, allowing methanotrophic bacteria to develop and to consume the entire methane emission 4 months later.